A noção de infância e suas implicações na atuação profissional de peritos psicólogos à luz de um aporte fenomenológico - OLIVEIRA, Alexsandro Augusto Carvalho de (2018)
The historical constitution on the notion of childhood reveals a plurality of elements linked to cultural, political, scientific and institutional aspects. Add to this is the human perspective on understanding of the particularities intrinsic to the phenomenon of childhood and its crossings. Because of this, the present research project had as main objective to investigate, in the light of a phenomenological contribution, as expert psychologists who operate in cases of suspicious violence against children understand the phenomenon of childhood and their implications in the professional performance. As specific objectives, it was sought to present the historical constitution of the notion of childhood and its consequences in institutional practices to combat violence against children; to identify practices and procedures carried out by the expert psychologists of the Center for Technical Expertise for Children and Adolescents (CPTCA) in the State of Maranhão; and, finally, to analyze the narrative of expert psychologists of the CPTCA on childhood and possible implications in their professional performance for a phenomenological bias. This theme arose from concerns about the activities developed by the researcher himself in his work as an expert psychologist at the CPTCA. In order to reach the proposed objectives, we present, initially, considerations about the notion of childhood in several fields of knowledge; reflections on the possibility of a rigorous knowledge about childhood from the phenomenology of Merleau-Ponty; indicatives of the relation between Childhood and State in the history of Brazil; in addition to discuss the role of the CPTCA psychologist expert in child protection. The research developed is of a qualitative nature and the narratives of the expert psychologists were collected over interviews with the experts through a semi-structured script, with socio-professional data and a triggering question. The narratives were analyzed using the Experimental Phenomenological Method from Amedeo Giorgi. From the narratives of the psychologists experts emerged units of meaning related to childhood perspectives, to the development and formation of the child, to the characterization of childhood and child, to the child present in psychological expertise, to violence in childhood and to the influences of the socio-political context in the childhood. It is hoped that this study may contribute with reflections, along with professional expert psychologists and others interested in the matter, on the importance of the elements that constitute the Childhood, considering the complexity of the violence and its implications in this phenomenon.